Induced transtensional earthquakes after the 1999 Chi-Chi earthquake in the compressional collision belt of western Taiwan - Lee, Timothy Ting-Yu (2018)
Static stress changes after major earthquakes are generally believed to influence the spatial and/or temporal distribution of aftershocks and subsequent earthquake events. Aftershock sequences, for example, tend to occur in areas with an increase in Coulomb stress with similar mechanisms to the main shock. However, in regions with pre-existing crustal structures with different mechanisms, the corresponding Coulomb stress change may result in different seismic characteristics. In this study, we demonstrate that a transtensional aftershock sequence was induced by the 1999 Chi-Chi earthquake on a pre-existing normal fault, in the compression-dominated western Taiwan fold-and-thrust belt. We used relocated seismicity and earthquake focal mechanisms to show that this sequence is likely occurred along a subsurface fault that strikes N10°W and dips 80° to the east, at depths greater than 5 km. A Coulomb stress change analysis also shows that this aftershock sequence were located in the area of stress increase due to the Chi-Chi earthquake. Such pre-existing normal faults are found throughout the western coastal plains of Taiwan, thus may pose important earthquake hazards for the populous cities located in the area.